GR_GERICHTE PZ 2004 31 vom 3. Mai 2004 , Vollstreckbarkeit und Vollzug (ZPO 263) - GR Gerichte (2004)
Amtsbefehl (Besitzesschutz) | Leitentscheid, publiziert als PKG 2004 24\x3Cbr\x3E | Amtsbefehl/Amtsverbot (ZPO 152/154)